Impact of the covid-19 pandemic on the psychological status and cortisol level of multiple sclerosis patients - Hatef, Boshra; Pirzad Jahromi, Gila; Meftahi, Gholam Hossein; Shaygan, Vahid; Ghalavand, Majdedin (Neuropsychological rehabilitation, 2023)
This study aimed to compare the changes in psychological status and cortisol level between multiple sclerosis (MS) patients and a healthy control group (HC). One hundred and fifty-five MS patients and 165 HC subjects had completed questionnaires consisting of 36-Item short health survey (SF-36), Hamilton Anxiety Rating Scale (HAM-A), Beck Depression Inventory-II (BDI-II), and fatigue severity score (FSS) before and after (one year from onset) COVID-19 pandemic. The salivary cortisol level was also measured again in 26 MS patients and 14 control individuals. MS patients had lower scores of mental and physical components of quality of life (MCS and PCS), but higher HAM-A, FSS, and BDII scores than HC Before and after COVID-19. There were significant changes in scores of MCS, BDI-II, HAM-A, and FSS after the COVID-19 outbreak in MS patients, but not in PCS score. In HC group, we observed significant changes in scores of MCS, BDI-II, and FSS, but not in scores of PCS and HAM-A. Compared to HC, the MS patients reported greater deterioration in the overall mental health component of their health-related quality of life, and their levels of anxiety and fatigue over the study period. The change of cortisol levels was non-significant with a small effect size.